Two new species of striped Pseudochromis from the Philippine Islands and Indonesia, with a redescription of P. colei (Perciformes: Pseudochromidae) - Gill, Anthony C.; Allen, Gerald R.; Erdmann, Mark (Zootaxa, 2012)
Pseudochromis ammeri sp. nov. and P. eichleri sp. nov. are described from Indonesia (Raja Ampat Islands, West Irian andHalmahera) and the Philippines (Calamianes Group, Boracay and northern Palawan), respectively. In having in combina-tion a dark longitudinal stripe on the body and the anterior tip of the palatine tooth patch directed medially behind poste-rolateral arm of vomerine tooth patch, the two species closely resemble P. colei Herre from the Philippines. The latterspecies is redescribed on the basis of the holotype from Culion and two specimens recently collected in northern Palawan. The three species closely resemble each other but differ in live coloration and several scale count characters.